Male engagement guidelines in antenatal care: unintended consequences for pregnant women in Tanzania - Haika Osaki; Saumya S. Sao; Godfrey A. Kisigo; Jessica N. Coleman; Rimel N. Mwamba; Jenny Renju; Blandina T. Mmbaga; Melissa H. Watt (BMC, 2021)
Abstract Background The meaningful engagement of male partners in antenatal care (ANC) can positively impact maternal and newborn health outcomes. The Tanzania National Plan for the Elimination of Mother to Child Transmission of HIV recommends male partners attend the first ANC appointment as a strategy for HIV prevention and treatment. This recommendation seeks to increase uptake of HIV and reproductive healthcare services, but unintended consequences of these guidelines may negatively impact women's ANC experiences. This study qualitatively examined the impact of policy promoting male engagement on women's ANC experiences. Methods The study was conducted in two urban clinics in Kilimanjaro Region, Tanzania. In-depth interviews were conducted with 19 participants (13 women and 6 male partners) attending a first ANC appointment. A semi-structured guide was developed, applying Kabeer's Social Relations Approach. Data were analyzed using applied thematic analysis, combining memo writing, coding, synthesis, and comparison of themes. Results Male attendance impacted the timing of women's presentation to ANC and experience during the first ANC visit. Women whose partners could not attend delayed their presentation to first ANC due to fears of being interrogated or denied care because of their partner absence. Women presenting with partners were given preferential treatment by clinic staff, and women without partners felt discriminated against. Women perceived that the clinic prioritized men's HIV testing over involvement in pregnancy care. Conclusions Study findings indicate the need to better assess and understand the unintended impact of policies promoting male partner attendance at ANC. Although male engagement can benefit the health outcomes of mothers and newborn children, our findings demonstrate the need for improved methods of engaging men in ANC. ANC clinics should identify ways to make clinic settings more male friendly, utilize male attendance as an opportunity to educate and engage men in pregnancy and newborn care. At the same time, clinic policies should be cognizant to not discriminate against women presenting without a partner.